PENGARUH PERSEPSI RESIKO, PENGETAHUAN, KEMUDAHAN TERHADAP MINAT MENGGUNAKAN MOBILE BANKING SYARIAH - Hayatullah; Arsa; Eri Nofriza (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of information technology has brought significant changes to various activities, including banking activities. One form of technological development is mobile banking, which allows customers to conduct banking transactions quickly and conveniently through mobile phones. However, the use of mobile banking is influenced not only by the benefits offered but also by people's perceptions of its ease of use and risks. This study aims to determine the effect of perceived ease of use and risk on people's intention to use Islamic mobile banking services among the residents of Sungai Putri Village, Danau Sipin District, Jambi City. This study employed a quantitative approach, with data collected through questionnaires. The population consisted of residents of Sungai Putri Village aged at least 18 years who used or had used mobile banking. Based on the Slovin formula with a 5% error tolerance, a sample of 45 respondents was obtained. Data analysis was conducted using validity and reliability tests, classical assumption tests, multiple linear regression, t-test, F-test, and coefficient of determination. The results show that perceived ease of use has a significant effect on the intention to use mobile banking, with a t-value of 4.117 > 1.984 and a significance value of 0.000 < 0.05. Risk also has a significant effect on the intention to use mobile banking, with a significance value of 0.000. Simultaneously, perceived ease of use and risk significantly affect the intention to use mobile banking, with an F-value of 43.324 > 3.09 and a significance value of 0.000 < 0.05. The Adjusted R Square value of 0.461 indicates that 46.1% of the variation in intention to use mobile banking is explained by perceived ease of use and risk, while the remaining 53.9% is explained by other factors outside the study